Improved thermomechanical and viscoelasticity properties of bio-epoxy/date palm fiber composite by addition of eggshell particles - Siti Noorbaini, Sarmin; Jawaid, Mohammad; Ahmad Safwan, Ismail; Fouad, Hassan; Dhakal, Hom; Nurjannah, Salim; Singh, Balbir; Hashem, Mohamed Ibrahim (Taylor and Francis Ltd., 2023)
In this research, a novel eco-friendly green composite is fabricated by combining a biomatrix composed of a biopolymer, date palm fiber, and a filler obtained from discarded eggshell (ES) waste material. This research aims to check the influent of ES filler on thermal and viscoelasticity properties of bio-epoxy composite with incorporation of 40 wt.% date palm (DP) fiber. Various ES filler ratios, specifically 5 wt.%, 10 wt.%, 15 wt.%, and 20 wt.%, are dispersed into the composite. Thermogravimetric analysis (TGA) and dynamic mechanical analysis (DMA) approach were employed to investigate the properties of fabricated composites as a function of temperature in terms of storage modulus (E′), loss modulus (E′′), Tan delta (Tan δ), glass transition temperature (Tg), and Cole-Cole plot. Overall, incorporating ES filler into the bio-epoxy/DP fiber composites increased E′, E′′, and Tg significantly. ES-filled composites containing 5 and 10 wt.% exhibited properties comparable to 15 wt.% but less than 20 wt.% ES filler. Thermal tests result show that 20 wt.% ES-filled materials outperform their counterparts in terms of heat resistance or thermal stability. The evidence suggests that the embodiment of ES filler in bio-epoxy/DP fiber composites yields enhancements in both thermal and dynamic mechanical properties. This indicates the potential for utilizing ES filler loading in advanced composite applications that prioritize thermal stability and sustainability.